Haplo-stem cell transplant post liver transplantation to cure sickle cell disease with related liver dysfunction: a case series - Ali D. Alahmari; Saad Alghamdi; Reem Alasbali; Sara Hisham Samarkandi; Saleh Algahtani; Hadeel Samarkandi; Syed Osman Ahmed; Dieter Broering; Hazzaa Alzahrani; Adetola Kassim; Mahmoud Aljurf; Fahad Almohareb; et al. (Communications Medicine)
Abstract Background Sickle cell disease (SCD) is debilitating, with age-dependent complications such as stroke and liver disease, leading to significant morbidity and early mortality in young adults. Hematopoietic stem cell transplantation (HCT) is curative treatment for SCD, but transplantation-related risks often deter its use, especially in patients with severe comorbidities. A subset of severe SCD patients with significant end-organ dysfunction may benefit from a combined approach of HCT and solid organ transplantation (SOT). Methods To the best of our knowledge, this report presents, for the first time, the utilization of dual orthotopic liver transplantation and haploidentical HCT (haplo-HCT) for severe SCD with advanced liver cirrhosis. Employing nonmyeloablative conditioning regimen and post-transplantation cyclophosphamide (PTCy). Results Both patients undergo orthotopic liver transplantation followed by haplo-HCT from the same related donors, achieve stable allograft function, full donor engraftment, and successful immunosuppression withdrawal through immune tolerance induction. Conclusions Dual haplo-HCT and living donor liver transplantation (LDLT) is feasible in eligible SCD patients with end-stage liver disease.